Toll-like receptor function in primary B cell defects - Marron, Thomas U. (2012)
Primary immunodeficiency diseases include more than 150 different genetic defects, classified on the basis of the mutations or physiological defects involved. The first immune defects to be well recognized were those of adaptive immunity affecting B cell function and resulting in hypogammaglobulinemia and defects of specific antibody production; more recently, novel defects of innate immunity have been described, some involving Toll-like receptors (TLRs) and their signaling pathways. Furthermore, it is increasingly evident that the innate and adaptive pathways intersect and reinforce each other. B cells express a number of TLRs, which when activated lead to cell activation, up-regulation of co-stimulatory molecules, secretion of cytokines, up-regulation of recombination enzymes, isotype switch and immune globulin production. TLR activation of antigen presenting cells leads to heightened cytokine production, providing additional stimuli for B cell development and maturation. Recent studies have demonstrated that patients with common variable immunodeficiency (CVID) and X-linked agammaglobulinemia (XLA) have altered TLR responsiveness. We review TLR defects in these disorders of B cell development, and discuss how B cell gene defects may modulate TLR signaling.